Model 5E and teaching thermodynamics. Design and evaluation of a teaching-learning sequence - Zárate-Moedano, Ramón (2023)
[Objective] The objective of this investigation is to document the design, implementation and evaluation process of a teaching-learning sequence based on the 5E model for teaching the concepts of heat and temperature. [Methodology] Using a design-based research methodology, the implementation of a teaching-learning sequence was designed, implemented, and evaluated with secondary school students between 13 to 15 years old. Nineteen (19) students from two Mexican schools participated, organized into two groups, one from each school. Using a pretest –  posttest experimental design, quantitative data were recorded related to the students' knowledge about the use of the concepts of heat and temperature to explain natural phenomena, as well as qualitative data obtained during sessions with the students.  Quantitative data were analyzed using the Shapiro-Wilk test and two-factor ANOVA using JASP with p≤0.05. In addition, a triangulation with qualitative data was performed to support the conclusions. [Results] The results obtained showed positive effects related to the knowledge that students achieved during implementation of the sequence. Positive effects were also found in the qualitative evidence, where it was observed that the conceptual integration displayed by the students was sufficient to explain, in a coherent and complex way, the natural phenomena related to the concepts of heat and temperature. [Conclusions] The teaching-learning sequence achieved the proposed learning goals related to the concepts of heat and temperature. A list of design principles is included that is intended as a guide for other teachers interested in adapting this experience to their local contexts.